Dissociative disorders in children – literature review - Monika Nowak; Michał Szyszka; Wiktoria Lewicka (Pediatria Polska, 2023)
Dissociative disorders (DD) are mental disorders that involve experiencing a disconnection and lack of continuity between thoughts, memories, surroundings, actions, and identity. Transient dissociative episodes are a common phenomenon during childhood that generally decrease during adolescence to relatively low levels in adults. There is strong evidence that traumatic events play a key role in the development of dissociation, but non-abusive and genetic factors are also considered. In the article, we discuss a few complementary theoretical models of the origin of DD that view them from attachment theory, affect theory, or developmental perspectives. Diagnosing DD among children is especially hard because of their frequent co-occurrence with other disorders, their broad differential diagnosis spectrum, and the fact that symptoms may be unnoticed for a long time. Treatment guidelines are mainly based on experts’ opinions, so appropriate studies on children are necessary.